Motivation of trainee teachers in conducting online learning using digital games based on arcs motivation model - Laili Farhana Md Ibharim; Mohammad Azri Mohd Shukuri (Penerbit Universiti Kebangsaan Malaysia, 2022)
The endemic situation of Covid-19 plaguing the world today has huge implications for education. This requires teachers to be more creative and innovative in delivering knowledge in the classroom via online learning. However, trainee teachers lack experience and skills compared to professional teachers, which affects the consistency of their motivation. Therefore, this paper discusses the perceived improvement of motivation of trainee teachers based on the ARCS motivation model toward a game-based learning approach through a digital game called StayFit as a teaching tool. This study focuses on four components of ARCS motivational constructs;- i) attention; ii) relevance; iii) confidence; and iv) satisfaction. The research design is quantitative and based on a survey using a questionnaire to collect the data. 56 respondents were involved in this study and the data were analysed using descriptive statistics. The results of this study show that the trainee teachers gave positive feedback through the implementation of digital game-based learning in their online classes especially in terms of enhancing their motivation in the teaching process. The implication of the study shows that the use of digital game as a teaching aid in online learning can increase the motivation of trainee teachers and make the learning process more effective, which meet with the needs of remote learning that applied during this endemic situation.